Control interno y su incidencia en los estados financieros de la Liga Cantonal de Urdaneta año 2020-2021. - Rizo García, Luisa María (2022)
The objective of this research work is to analyze the internal control system and its impact on the financial statements and finally verify that the objectives and policies of the entity are met, based on the financial statements. This investigation is justified based on the analysis of internal control in the financial statements will help the Cantonal Sports League of Urdaneta to make adequate decisions, as well as facilitate the work of audits, whether management or financial, in turn will allow to examine the current presentation of the financial statements and how to improve this process.